The Relationship between religious orientation and promotion of sexual satisfaction and marital satisfaction in women of reproductive age - Fateme Bozhabadi; Atefe Beidokhti; Fateme Shaghaghi; Ali Parimi; Zahra Kamali; Mahboobe Gholami (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Marital satisfaction is a situation in which the husband and wife enjoy marrying and feeling emotional; on the other hand, the existence of religious beliefs has a significant effect on family stability. The aim of this study was to determine the relationship between religious orientation, sexual satisfaction, and marital satisfaction in women of reproductive age. METHODS: This is a correlational study performed on 150 married women aged 45-45 years who referred to Neyshabur comprehensive health services centers. The sampling method was clustered. The present study used three questionnaires: Spinner Marital Satisfaction, Larson's Sexual Satisfaction, and Allport Religious Orientation Questionnaire. The reliability of these questionnaires was confirmed by the retest method. T-test, Pearson correlation, and one-way ANOVA were used for data analysis. RESULTS: Data analysis showed that there is a significant and positive relationship between religious orientation and sexual satisfaction and marital satisfaction. Religious commitment has a predictive role in promoting sexual satisfaction and marital satisfaction, with increasing religious commitment, increasing sexual satisfaction, and marital satisfaction. CONCLUSION: Psychologists and counselors in individual and couple counseling sessions with sexual problems and marital dissatisfaction and premarital counseling can increase marital satisfaction with regard to religious factors and religious and spiritual teachings.